Be Happy, Be Honest: The Role of Self-Control, Self-Beliefs, and Satisfaction with Life in Honest Behavior - Błachnio, Agata (Journal of religion and health, 2021)
Honesty seems to be a key value influencing how others perceive us and how we see ourselves. The aim of this study was twofold: to develop a questionnaire measuring honesty and to test whether certain psychological variables—self-control, self-beliefs, and satisfaction with life—correlate with honesty. The participants in the study were 693 individuals. The authors administered the Honesty Scale, the Brief Self-Control Scale, the Social Success Index, the Normalcy Feeling Scale, the Social Comparison Scale, and the Satisfaction with Life Scale. The analysis yielded three factors of the Honesty Scale, namely personal honesty, relational honesty, and honesty value. Additionally, the study revealed that honesty was positively correlated with self-control, normalcy feeling, and satisfaction with life. Research on honesty has made it possible to better understand human behavior in various aspects of life. Future directions for research are also discussed.